2012
DOI: 10.3961/jpmph.2012.45.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Ferritin and Transferrin % Saturation With All-cause, Cancer, and Cardiovascular Disease Mortality: Third National Health and Nutrition Examination Survey Follow-up Study

Abstract: Objectives Even though experimental studies have suggested that iron can be involved in generating oxidative stress, epidemiologic studies on the association of markers of body iron stores with cardiovascular disease or cancer remain controversial. This study was performed to examine the association of serum ferritin and transferrin saturation (%TS) with all-cause, cancer, and cardiovascular mortality. Methods The study subjects were men aged 50 years or older and postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 29 publications
(38 reference statements)
3
28
0
Order By: Relevance
“…[18][19] Given that CRP and albumin also predict mortality from any cause, cancer, cardiovascular disease and cerebrovascular causes, it may be that the association of measures of iron status and mortality is dependent on the presence of systemic inflammation. 20 Further work is required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19] Given that CRP and albumin also predict mortality from any cause, cancer, cardiovascular disease and cerebrovascular causes, it may be that the association of measures of iron status and mortality is dependent on the presence of systemic inflammation. 20 Further work is required to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have indeed shown a correlation between the incidence and mortality of cancer and systemic iron levels, as measured by transferrin saturation or serum ferritin, this correlation is generally not strong, has shown conflicting outcomes, and it is often confounded by the presence of other pathology88,89. There is, however, clear evidence that deregulated iron homeostasis on a local — that is, microenvironmental and/or cellular — level is associated with tumour progression, as illustrated by changes in expression of iron-related genes in cancer cells (Figure 4), the levels of which are inversely correlated with patient survival9092.…”
Section: Iron and The Pathophysiology Of Diseasementioning
confidence: 99%
“…Serum ferritin was not prognostic in melanoma patients treated with adjuvant interferon-alfa,16 nor in operable breast cancer 17. Population based epidemiological research also did not support the association of serum ferritin with cancer mortality either 18,19. It seems that the prognostic significance of serum iron metabolism parameters is dependent on both tumor-type and clinical context.…”
mentioning
confidence: 89%